Pemahaman Konsep Matematis Siswa Sekolah Menengah Pertama: Pengaruh Explicit Instruction Ditinjau dari Self-Reliance - Jeni Safitri; Bambang Sri Anggoro; Abi Fadila; Wahyu Nofiansyah (Arithmetic)
The purpose of this study was to determine the effect of the explicit instruction learning model on the understanding of mathematical concepts in terms of self-reliance of junior high school students. This research uses quantitative research with Quasi Experimental Design research. The results of the study indicate that: 1) there is an influence between the Explicit Instruction learning model and the expository learning model on understanding mathematical concepts. Then students' understanding of mathematical concepts in the application of the expository learning model is no better than students' understanding of mathematical concepts in the application of the Explicit Instruction learning model; 2) there is no influence between students with high, medium, and low self-reliance categories on understanding mathematical concepts; 3) there is no interaction between learning model factors and self-reliance towards understanding mathematical concepts. The recommendation is that the application of the Explicit Instruction learning model can be an alternative in learning mathematics, especially in maximizing understanding of mathematical concepts for other discussions and can also maximize students' self-reliance.